Impacts of International Migration and Remittances on Child Outcomes and Labor Supply in Indonesia : How Does Gender Matter? - Nguyen, Trang; Purnamasari, Ririn (2012)
This paper aims to investigate empirically how international migration and remittances in Indonesia, particularly female migration, affect child outcomes and labor supply behavior in sending households. The authors analyze the Indonesia Family Life Survey data set and apply an instrumental variable estimation method, using historical migration networks as instruments for migration and remittance receipts. The study finds that, in Indonesia, the impacts of international migration on sending households are likely to vary depending on the gender of the migrants. On average, migration reduces the working hours of remaining household members, but this effect is not observed in households with female migrants. At the same time, female migration and their remittances tend to reduce child labor. The estimated impacts of migration and remittances on school enrollment are not statistically significant, but this result is interesting in that the directions of the effects can be opposite when the migrant is male or female